Aspects of complexity : managing projects in a complex world - Cooke-Davies, Terry, 1941-; Crawford, Lynn (Project Management Institute, 2011)
Presents advice on using project management techniques to successfully identify and manage complex processes or events which could impact project timelines and costs.